STUDI EFFEKTIVITAS KEFIR BENING DAN MENIRAN (Philanthus niruri) TERHADAP PENURUNAN KADAR GLUKOSA DARAH PADA HEWAN TIKUS WISTAR HIPERGLIKEMIA DIINDUKSI STREPTOZOTOCIN - ., Judiono; Hadisaputro, Soeharyo; Djokomoeljanto, RRJ; Laksono, Budi; W, Theophilus (GIZI INDONESIA, 2010)
EFFECTIVITY STUDY OF PLAIN KEFIR AND MENIRAN (PHILANTUS NIRURI) ON BLOOD GLUCOSE LEVELS ON HYPERGLYCEMIA WISTAR RATS INDUCED STREPTOZOTOCINTraditional medicines and functional foods used for diabetes therapy increased in Indonesia. Bioactive components play an important role in decreasing blood glucose. The study aims to prove the effectiveness of plain kefir and Meniran (Philanthus niruri) to decrease blood glucose levels in wistar rats with streptozotocin-induced hyperglycemia. The study design was randomized pre – post test control group. A number of 60 male rats aged 2.5-3 months, 150-250 g were made hyperglycemia by induced streptozotocin (STZ) 40 mg / kg berat badan. The hyperglycemic rats were grouped into: (1) treated with 0.76 UI insulin /day, (2) treated with 3.6 mL plain kefir /day, (3) treated 2.7 mL meniran / day, (4) positive control group of hyperglycemic rats, and (5) negative control group (standard diet ad libitum). The ratswere given feed refers to the AIN 93. Fasting glucose levels before and after treatment were measured by Super (Glucocard II) enzimatic method. The results showed that body weight increased in all treatments, except meniran, however the increaments were not differ significantly. Changes in body weight of insulin group were 13.800 + 16.104 g, kefir treatment amounted to 13.812 + 21.294, and meniran increased about 18.394 + 16.225. Changes in blood glucose in the insulin group about -118.571+55.815 mg/dL, kefir treatment at -102.875+60.454, while meniran group -66,625+37,784. In contrast, the positive control group tended to increase glucose levels. Conclusion In vitro, plain kefir and meniran potentially lowered blood glucose levels. However, kefir showed lowered glucose level better than meniran. Futher research needs to study bio- molecular mechanisms of the decline in the future.Key words: diabetes mellitus, meniran, plain kefir, streptozotocin (STZ), hyperglycemic rat